A Semantic Analysis of Denotative and Connotative Meanings in the Song "Someone Like You" by Adele - Rentina Flora Indah Ompusunggu; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study investigates the denotative and connotative meanings embedded in the lyrics of "Someone Like You" by Adele, a globally acclaimed pop ballad released in 2011. Drawing upon Leech's (1981) semantic framework and Ullmann's (1962) theory of meaning, this qualitative research employs a descriptive-analytical approach to examine the lyrical content. The data were collected through purposive sampling of the song's complete lyrics, and were analyzed using content analysis methods. The findings reveal that the lyrics contain rich layers of both denotative meanings—referring to literal, dictionary definitions—and connotative meanings, which evoke emotional, cultural, and associative significance beyond the literal sense. Key themes identified include grief, longing, acceptance, and unresolved romantic attachment. The study demonstrates that Adele's strategic use of language creates a multidimensional semantic landscape that resonates universally with listeners' emotional experiences. This research contributes to the growing body of literature on semantic analysis in popular music and offers pedagogical implications for English language teaching through song lyrics.